2021
DOI: 10.2174/1745017902117010061
|View full text |Cite
|
Sign up to set email alerts
|

Managing Problematic Usage of the Internet and Related Disorders in an Era of Diagnostic Transition: An Updated Review

Abstract: Introduction: Problematic Usage of the Internet (PUI) refers to a broad and likely heterogeneous group of Internet-related conditions associated with behavioural disturbances and functional impairment. Methods: Within PUI several conditions have been reported, including Gaming Disorder, Shopping Addiction, Cyberchondria, Gambling Disorder, Cyberpornography Addiction and Cyberbullying. While increasing reports in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 157 publications
(175 reference statements)
0
10
0
Order By: Relevance
“…In addition, a diagnostic specifier of 'online' (as opposed to offline) activity was added. However, PUI describes excessive online activities associated with marked functional impairment and/or distress, which may include not only gaming and gambling but also online buying or shopping, cybersex/pornography use [24], social media use [25], cyberchondria, digital hoarding, cyberstalking, and excessive use of online streaming with addictive, impulsive and/or compulsive features [26]. A further new ICD-11 diagnosis for Other Specified or Unspecified Disorders Due to Addictive Behaviours was created to allow for potential diagnosis of some of these problematic behaviours as disorders, should the extent of the problem meet the specified diagnostic criteria.…”
Section: Reliable Consensus-driven Conceptualisation Of Puimentioning
confidence: 99%
“…In addition, a diagnostic specifier of 'online' (as opposed to offline) activity was added. However, PUI describes excessive online activities associated with marked functional impairment and/or distress, which may include not only gaming and gambling but also online buying or shopping, cybersex/pornography use [24], social media use [25], cyberchondria, digital hoarding, cyberstalking, and excessive use of online streaming with addictive, impulsive and/or compulsive features [26]. A further new ICD-11 diagnosis for Other Specified or Unspecified Disorders Due to Addictive Behaviours was created to allow for potential diagnosis of some of these problematic behaviours as disorders, should the extent of the problem meet the specified diagnostic criteria.…”
Section: Reliable Consensus-driven Conceptualisation Of Puimentioning
confidence: 99%
“…Studies on clinical populations are scarce. However, it has been suggested that cyberchondria could be a transdiagnostic factor present in several clinical conditions such as PUI, health-related anxiety that may present as generalized anxiety disorder, hypochondriasis, and OC disorder (OCD) [ 15 ]. However, few studies have considered to date cyberchondria as a potentially addictive behavior, although frameworks such as the interaction of person, affect, cognition, and execution (I-PACE) may apply to cyberchondria as it does other addictive disorders [ 9 , 10 ], as might the designation of “other specified disorder due to addictive behaviors” listed in the eleventh revision of the International Classification of Diseases [ 11 ].…”
Section: Cyberchondriamentioning
confidence: 99%
“…In previous work, our group tentatively proposed a "working" definition of CYB [17] based on existing definitions of CYB -reflecting three key components: 1) the compulsive nature of online health searching; 2) an increase in anxiety or distress during or after the searching; 3) the negative impact on other online and offline activities. This definition reflects a conceptualization J o u r n a l P r e -p r o o f of CYB as a compulsive form of Problematic Usage of the Internet (PUI) [18,19], an emerging group of disorders that are currently conceptualized within a framework of behavioural addiction and in which framework loss of inhibitory cognitive control over impulsive as well as compulsive responding is emphasized. Indeed, CYB and PUI share in common the distressing loss of control over urge-driven online activity, resulting in time-consuming, compulsive behaviour, that is continued despite acknowledgement of negative consequences and that ultimately causes distress or impairs functioning.…”
Section: Natural History Of Cyberchondriamentioning
confidence: 99%